Validity and Reliability of Teacher Work Satisfaction Scale: The Validity and Reliability of Teacher Work Satisfaction Scale - Rara Salsabila Syani; Tentama, Fatwa; Diponegoro, Ahmad Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
The purpose of this research is to test the validity and reliability, as well as to test the aspects that can form the job satisfaction variables which are compiled based on the Spector theory. Job satisfaction is measured based on nine aspects, pay, promotion, fringe benefits, rewards, supervision, work procedures, co-workers, nature of work, and communication. The subjects of this study were 86 teachers of SMK Muhammadiyah in Yogyakarta. The scale was compiled using a semantic differential scaling model and the data were analyzed using Structural Equation Modeling (SEM) through the SmartPLS 3.0 program. The results showed that all aspects were able to reflect job satisfaction variables. The dominant aspect is the aspect of supervision with a loading factor value of 0.798. While the weak aspect is the aspect of the nature of the job with a loading factor value of 0.612.